Peningkatan Literasi Digital Melalui Pelatihan Pengelolaan Website Di Pondok Pesantren Salafiyah Iqro Palangkaraya - Windiarti, Ika Safitri; Miftahurrizqi; Haryanto, Dwi (LPPM UMRI, 2022)
The Salafiyah Islamic Boarding School (PPS) IQRO does not yet have a website to support the learning process and promote IQRO PPS to parents of prospective students, donors, partners, government, and other organizations. The implementation team and partners have held discussions to address these problems. To deal with the first problem, the first thing to do is to do a Need Analysis or needs analysis from PPS IQRO related to the website. Need Analysis will be conducted with Focus Group Discussion (FGD) involving elements of managers, teachers, and students, as well as several community leaders. The solution that has been agreed upon is to first design a profile website based on the results of the Need Analysis and FGD. After that website development for partners. To overcome the second and third problems is to conduct training on the development and management of profile websites and learn about the elements found in partners. The solution that has been agreed upon is to schedule the training, which is preceded by a Pre-Test and ends with a Post-Test to determine the level of understanding and skills. In addition, there will be assistance for the next 3 years in managing the website.